Arabian Mirrors and Western Soothsayers: Nineteenth-Century Literary Approaches to Arab-Islamic History by Muhammed A. Al-Da'mi (New York: Peter Lang, 2002. 235 pages.) (American Journal of Islam and Society, 2003)
This is a superb book. With penetrating insight and an eloquent style, alDa'miexplores the crucial role that Arabo-lslamic history played in thearguments of such prominent British and American "men of letters" asThomas Carlyle and Washington Irving. The book opens with a preface,in which he lays out his rationale and purpose, and contains seven chapters,in which he develops his argument.AI-Da'mi seeks to deepen our understanding of nineteenth-centuryOriental ism by exploring the works of leading intellectual writers of thattime: not the professional historians, but the "men ofletters" who used historyto expound their arguments, but with a kind of literary licence notavailable to a proper historian. His main argument is that the writers usedArabo-Islamic history not simply as an exotic or a romantic flourish, butrather as an integral and important aspect of their discourses to commentupon their own time. For example, Carlyle praises the Prophet as a heroicleader, as a way to warn the British of the dangers of utilitarianism andmaterialism; Ralph Waldo Emerson likewise does this to send a messageto the young American nation; Cardinal John H. Newman to alert Europeto the Ottoman threat; and so on.Al-Da'mi convincingly points out that we can neither understandthese writers nor the age itself adequately without properly comprehendingthis aspect of their writings. This is an important rectification to traditionalwestern scholarship, which typically leaves out all mention ofanything non-European in its study of its own intellectual history. (WalterE. Houghton's classic work on the Victorian age, The Victorian Frame ofMind, 1830-1870, has in its index only one entry for Prophet Muhammad ...